2004
DOI: 10.1111/j.1365-2958.2004.04319.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐guided nucleotide modification of ribosomal and non‐ribosomal RNAs in Archaea

Abstract: SummaryArchaea use ribonucleoprotein (RNP) machines similar to those found in the eukaryotic nucleolus to methylate ribose residues in nascent ribosomal RNA. The archaeal complex required for this 2 ¢ ¢ ¢ ¢ -O-ribosemethylation consists of the C/D box sRNA guide and three proteins, the core RNA-binding aL7a protein, the aNop56 protein and the methyltransferase aFib protein. These RNP machines were reconstituted in vitro from purified recombinant components, and shown to have methylation activity when provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…In Eukarya, the homologous enzyme (called Trm3) is frequently fused to other domains whose functions are largely unknown (Cavaille et al 1999). In contrast, it has been reported that Gm18 formation in the archaeon Sulfolobus solfataricus involves a guide RNA (Ziesche et al 2004). Paralogs of TrmH are found in various bacteria (Anantharaman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eukarya, the homologous enzyme (called Trm3) is frequently fused to other domains whose functions are largely unknown (Cavaille et al 1999). In contrast, it has been reported that Gm18 formation in the archaeon Sulfolobus solfataricus involves a guide RNA (Ziesche et al 2004). Paralogs of TrmH are found in various bacteria (Anantharaman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Eukarya, mainly ribosomal RNA (rRNA) and small nuclear RNA (snRNA) are modified by guided MTases (Clouet-d'Orval et al 2005;Reichow et al 2007). In Archaea, several 2 ′ -O-MTases of rRNA and, to a limited extent, transfer RNA (tRNA) utilize the guided system (Ziesche et al 2004;Renalier et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…S75397, NP_342426, P58032) were amplified by PCR, cloned between the NcoI and BamHI sites of pET3d (L7Ae, Fib) or NcoI and EcoRI sites of pET28a (Nop5), and transformed in Escherichia coli. The recombinant proteins were thermoprecipitated and further purified by ion exchange and size exclusion chromatography as described by Ziesche et al (2004).…”
Section: Cloning Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…In a few archaeal species, several C/D sRNAs were predicted to target more than 23 tRNA positions for 2 0 -O-methylation (Clouet d'Orval et al 2001;Dennis et al 2001;Tang et al 2002;Omer et al 2003). Archaeal C/D RNP-guided tRNA 2 0 -O-methylations were recently demonstrated in vitro, on the Haloferax volcanii pre-tRNA Trp for C34 and U39 2 0 -O-methylation (Clouet d 'Orval et al 2001;Bortolin et al 2003) and on the S. solfataricus tRNA Gln for G18 methylation in an unique tRNA (Ziesche et al 2004). The absence of archaeal tRNA 2 0 -O-Mtases up until now raised the following question: Are all the tRNA 2 0 -O-methylations in archaea carried out by C/D box guide sRNPs?…”
Section: Introductionmentioning
confidence: 99%
“…Previous biochemical studies have shown that box C and D are the sites of RNP assembly (Szewczak et al 2002;Watkins et al 2002;Bortolin et al 2003;Decatur and Fournier 2003;Tran et al 2003). Archaeal C/D RNPs contain three proteins with a symmetric distribution: the archaeal fibrillarin (aFib), the ribosomal protein L7Ae and Nop5p (Kuhn et al 2002;Omer et al 2002;Watkins et al 2002;Aittaleb et al 2003;Bortolin et al 2003;Ziesche et al 2004). The box C/D sequences generate a characteristic RNA secondary structure motif, the kink-turn (K-turn) which is directly bound by L7Ae and, together with aFib and Nop5p, form the core RNP complex.…”
Section: Introductionmentioning
confidence: 99%